FRI0706-HPR COMPARISON OF IMPACT OF VERUM AND PLACEBO THUMB BASE ORTHOSES ON SKIN SURFACE TEMPERATURE AND PRESSURE : A PROOF OF CONCEPT STUDY. (June 2019) - Davis, Lois; Loyley, Marcus; Worsley, Peter; Adams, Jo
Abstract : Background: Basal thumb osteoarthritis (OA) can cause significant pain and cause a decline in hand function (Litwic et al 2013). Guidelines for treatment of symptomatic basal thumb OA supports a conservative approach, including splinting to support the carpometacarpal joint (CMCJ) and reduce the painful movements of the thumb joint during functional tasks (Zhang et al 2000). Lack of legitimate placebo thumb splint has been a barrier to research to distinguish the specific mechanism of the perceived therapeutic effect of wearing thumb splints. Despite this, splinting of the basal thumb joint remains a common intervention for pain. This research contributed to a national CRN portfolio adopted study examining the clinical effectiveness and efficacy of basal thumb splints for people with basal thumb OA. Objectives: In the present study, the efficacy of two novel placebo splint designs are examined in comparison to widely used verum thumb splint and no splint for the effect at skin surface interface whilst performing a functional task Methods: This proof of concept study used a single blind, cross-over design that assessed the effect of wearing different splint conditions on the skin surface interface during a functional hand task. 17 healthy participants (male n=8; female n=9) who met the inclusion criteria were recruited to take part in the study. Skin surface temperature (°C) and pressure exerted at the skin surface interface was recorded during performance of a standardised hand function task, the nine-hole peg test (9HPT) for four splint conditions i) verum splint (Promedics NC79562), ii) placebo lycra splint (P1); iii) placebo lycra splint "lite" (P2) and iv) no splint. Data were recorded and analysed by one rater using MatLab and SPSS software. Results: It was observed from the mean rank that the verum splint condition caused the greatest pressures compared to all other splint conditions. Post hoc analysis revealed there was no difference in pressure exerted over the CMCJ between the no splint condition and P1 (Z= -1.577, p=0.115) and P2 (Z= -0.365, p=0.715). The verum splint caused a significant increase in pressure over the CMCJ in comparison to all other test conditions (Z= -3.516, p<0.0005). ANOVA showed a significant effect of splint design on temp ( F (3, 16)= 22.96, p <0.05). Post hoc analysis revealed that the verum splint produced a significantly higher skin surface temperature (32.67°C ±1.10°C) than P1 (31.75°C ±1.10°C, p<0.0005), P2 (31.85°C ±1.11°C, p=0.001) and no splint (31.06°C ±1.24°C, p<0.0005) conditions. No differences in skin temperature was shown between placebo designs (p=1.00). Conclusion: This study is the first to characterise the effect of different thumb splint designs on the skin surface temperature and the mechanical loading force local to the CMCJ. This study further informs the specific effect of thumb splints at the joint interface. Identifying that new placebo splint designs do not provide additional support to the thumb joint is a novel supplement to research surrounding thumb splinting intervention and can support the use of these devices as placebo splint conditions in future trials. References: [1] Litwic A, et al. Epidemiology and burden of osteoarthritis. British medical bulletin. 2013Jan20;105(1):185-99 [2] Zhang W, et al. EULAR evidence based recommendations for the management of hand OA: report of a Task Force of the EULAR Standing Committee for International Clinical Studies Including Therapeutics (ESCISIT). Annals of the rheumatic diseases. 2007Mar1;66(3):377-88 Disclosure of Interests: None declared